2022
DOI: 10.1002/anie.202207055
|View full text |Cite
|
Sign up to set email alerts
|

Back Cover: ESA's Cometary Mission Rosetta—Re‐Characterization of the COSAC Mass Spectrometry Results (Angew. Chem. Int. Ed. 29/2022)

Abstract: The pace … …v isited the nucleus of comet 67P/Churyumov-Gerasimenko by placing the Philae lander on its surface.Philae was equipped with atime-of-flight mass spectrometer that analyzed, for the first time,c ometary surface material in situ. Fred Goesmann and coworkers describe in their Research Article (e202201925) the characterization of this mass spectrum through non-negative least square fitting and Monte Carlo simulations, revealing the chemical composition of cometary ices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Notably, a recent study has provided reanalysis of the data collected by the time-of-flight mass spectrometer COSAC 25 minutes after the initial touchdown of Rosetta's Philae lander unit on 67P's surface. This new study, published by Leseigneur et al (2022), updates previous results from Goesmann et al (2015) and explains the observed overall fragmentation pattern ranging from m/z = 12 to 63 with a suite of 12 molecules. These molecules have been identified with a high likelihood based on a least-squares fitting algorithm applied to a set of 120 preselected and partially "hand-picked" reference spectra.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Notably, a recent study has provided reanalysis of the data collected by the time-of-flight mass spectrometer COSAC 25 minutes after the initial touchdown of Rosetta's Philae lander unit on 67P's surface. This new study, published by Leseigneur et al (2022), updates previous results from Goesmann et al (2015) and explains the observed overall fragmentation pattern ranging from m/z = 12 to 63 with a suite of 12 molecules. These molecules have been identified with a high likelihood based on a least-squares fitting algorithm applied to a set of 120 preselected and partially "hand-picked" reference spectra.…”
Section: Discussionsupporting
confidence: 82%
“…Cyclopentanol does yield a minor amount of M, but tetrahydropyran, with its strong M and M-H signals, must be favored according to our method of analysis. The COSAC mass spectrum evaluated by Goesmann et al (2015) and Leseigneur et al (2022) was collected in the so-called sniffing mode, and it was assumed that, during first contact with the cometary surface, some excavated material entered the exhaust region of the instrument and evaporated there at local temperatures of 12 to 15 • C. Such conditions would be considerably different from those prevalent during the time when the DFMS data investigated in this work were collected, as ejected dust grains can reach temperatures of multiple hundreds of degrees Celsius in the coma (Lien 1990), and heavier species can sublimate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ethylene glycol was already found as one of the 16 molecules in the analysis of the “sniffing” mass spectrum taken by COSAC, [18] and confirmed to be one of the most likely molecules detected within that spectrum by recent research [19] . It has also been detected in the coma of 67P by the ROSINA DFMS instrument onboard the Rosetta orbiter [20] …”
Section: Resultsmentioning
confidence: 70%